Penggunaan Konjungsi dalam Teks Deskripsi Siswa Kelas VII SMP Negeri 41 Padang - Mita, Laras; Emidar, Emidar (Lembaga Yasin AlSys, 2023)
This research was carried out for two reasons, maely first to describe the types of conjuctions used in the description texts for class VII students of SMP 41 Padang. The second describe s how the use of conjuctions in the description text of class VII students of SMP 41 Padang. This type of research is qualitative with a describe method. This research was conducted at publick junior high school 41 Padang. The data of this research are sentences that use conjunctions in the description text og class VII students of SMP 41 Padang. The source of the data in this study was the descriptive text of class VII students of SMP 41 Paadang. Data is analyzed by classifying, analyzing, and discussing data based on theory technique. Based on the result of the research that has been done on the description text of class VII students of SMP 41 Padang, it can be conclude that first there at three types of conjuctions used in the description text of class VII students of SMP 41 Padang, namely coordinating conjunctions found as many as 133 conjunctions , subordinating conjunctions founs as many as 158 conjunctions , and conjuctions between sentences found 1 conjunctions. Both the use of conjuctions in the description text of class VII students SMP 41 Padang, found 36 inappropriate uses of coordinating conjunctions, 82 inappropriate uses of subordinating conjunctions , and 1 inappropriate use of inter sentences conjuctions. The percentage of inaccurary in the use of conjunctions in the descriptive text of class VII students of SMP 41 Padang is as follows. The percentage of inaccurary in the use of coordinating conjunction is 27,06% in the medium category, the percentage of inaccuary in the use of subordinating conjunctions is 51,89% in the high category. This is because students do not understand the use of conjunctions properly, besides that there are still many errors in writing conjunctions such as shortening the writing of conjunctions.